Linguistic Clarity in Mudharabah Contracts: Ensuring Transparency and Fairness in Indonesian Islamic Financial Institutions - Zaidi M, Zaidi (JOLLT Journal of Languages and Language Teaching, 2024)
This research aims to analyze the use of language in Sharia financial agreements, with a focus on a case study of mudarabah contracts. Sharia financial agreements play a crucial role in regulating financial transactions in accordance with Sharia principles. In the context of mudarabah contracts, the appropriate and clear use of language becomes a key aspect in maintaining transparency, clarity, and understanding among the parties involved. This research adopts a qualitative method with a case study approach. Research data is collected through document analysis, including mudarabah contract agreements in real practice. The data is then thematically analyzed, focusing on word selection, the use of characteristic clauses, sentence structure, and other language structures in mudarabah contracts. The results of the analysis indicate that the appropriate and clear selection of words in mudarabah contracts is important to reflect Sharia principles and maintain transparency. Furthermore, the use of characteristic clauses helps regulate profit sharing, loss sharing, and the responsibilities of the involved parties. Clear and structured sentence arrangements also ensure clarity and readability of the contract contents. Additionally, the use of distinctive Arabic language structures provides clarity in describing actions that have been taken and instructions that must be followed by the parties involved. This research contributes significantly to understanding the use of language in Sharia financial agreements, particularly in the context of mudarabah contracts. The findings of this research are expected to serve as a reference for practitioners and academics in developing effective Sharia financial agreements in accordance with Sharia principles.